2020
DOI: 10.3390/catal10111358
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Plasma for Process and Energy Intensification in Dry Reforming of Methane

Abstract: Plasma-assisted dry reforming of methane (DRM) is considered as a potential way to convert natural gas into fuels and chemicals under near ambient temperature and pressure; particularly for distributed processes based on renewable energy. Both catalytic and photocatalytic technologies have been applied for DRM to investigate the CH4 conversion and the energy efficiency of the process. For conventional catalysis; metaldoped Ni-based catalysts are proposed as a leading vector for further development. However; co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 150 publications
0
30
0
2
Order By: Relevance
“…The electron temperature in NTP is much higher than that of heavy particles. Therefore, NTP technology has a wide range of applications such as pollutant removal, nano-material synthesis, material surface modification, and fuel reforming [24,26].…”
Section: Overview Of Non-thermal Plasmamentioning
confidence: 99%
See 3 more Smart Citations
“…The electron temperature in NTP is much higher than that of heavy particles. Therefore, NTP technology has a wide range of applications such as pollutant removal, nano-material synthesis, material surface modification, and fuel reforming [24,26].…”
Section: Overview Of Non-thermal Plasmamentioning
confidence: 99%
“…The results show that when Ni/C catalyst is combined with plasma, the catalytic activity was enhanced and the reaction conversion rate increased. Pietruszka et al found that by combining plasma and Ni/γ-Al 2 O 3 , conversions of both CH 4 and CO 2 were increased due to the discharge heating of the catalyst [24]. Kim et al observed that with Ni/Al 2 O 3 catalyst, conversion of CH 4 was significantly higher than that of DBD without catalyst [45,50,52,53].…”
Section: Ni-based Catalyst Assisted With Dbd Plasma For Drmmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-thermal plasma is an ionized gas created in mild conditions by applying electric energy to a gas. The plasma route is preferable for future industrial exploitability as it could be easily scaled up and it provides higher production rates and feed flexibility [2]. It is a potentially crucial technology to develop future chemistry based on the use of renewable energy and that is suitable for distributed use [3].…”
Section: Introductionmentioning
confidence: 99%